Electronic connector handbook theory and applications - Mroczkowski, Robert S. (Electronic packaging and interconnection series, 1998)
Including data on connectors, this handbook covers the basic functions of connectors and details the range of electronic connectors. It discusses connector parameters in an application context to expedite implementation, and provides design and materials selection criteria for the range of connectors.